Measurable Dynamic Gains from Trade - Richard Baldwin (The Research Institute of Industrial Economics (IUI), 1990)
Productive factors such as human and physical capital are accumulated and trade can affect the steady-state levels of such factors. Consequently, trade liberalization will have dynamic effects on output and welfare as the economy moves to its new steady state, in addition to its usual static effects. The output impact of this dynamic effect is measurable and appears to be quite large. The welfare impact of this dynamic effect is also measurable. The size of this dynamic gain from trade depends on the importance of external scale economies.
Keywords: D60; F11; 330; Trade liberalization; Gains from trade; Welfare